Economic impact of removing pigs before marketing on the remaining pigs’ growth performance - Jacela, J.Y.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
The economic impact of removing the heaviest pigs (topping) before marketing a finishing group and the effect of topping on performance of the remaining pigs were determined in 2 studies. In Exp. 1, a total of 1,126 pigs (BW = 241 lb; 25 pigs/pen) were randomly assigned to 1 of 3 treatments: topping 0, 2, or 4 pigs/pen 15 d before marketing the remaining pigs in the group. After topping, floor space per pig was 7.2, 7.8, and 8.6 ft2 for pens with 0, 2, and 4 pigs topped per pen, respectively. Overall (d 0 to 15), increasing the number of pigs topped per pen improved ADG (P < 0.02), ADFI (linear; P < 0.03), and F/G (quadratic; P < 0.04). Revenues were similar (P > 0.76) between treatments, but feed usage and cost was reduced (quadratic; P < 0.01) as more pigs were topped per pen. However, there was no impact on income over feed cost (IOFC). In Exp. 2, a total of 1,084 pigs (BW = 234 lb; 27 pigs/pen) were assigned to 1 of 5 treatments. On d 0 (20 d before closeout), 2 pigs were topped from each pen excluding the control pens (0 top). Pens that were topped at d 0 had an additional 0, 2, 4, or 6 pigs per pen topped on d 10. Floor space per pig was 6.7 ft2 in control pens and 7.2 ft2 for the remaining pens from d 0 to 10. After topping on d 10, floor space per pig was 7.8, 8.6, and 9.5 ft2 for pens with 2, 4, or 6 more pigs topped, respectively. From d 10 to 20, the remaining pigs had increased (linear; P < 0.01) ADFI, which led to a linear increase (P < 0.01) in ADG. Overall, ADG and ADFI increased (linear; P < 0.05) with increasing number of pigs topped, and F/G improved (P < 0.01) in topped pens relative to intact pens. Weight discounts were highest in intact pens (P < 0.02) compared to topped pens. Revenue decreased (P < 0.05) as additional pigs were topped after d 10 in pens topped at d 0. Feed usage was highest (P < 0.01) in intact pens. As more pigs were topped on d 10, IOFC tended to decrease (P = 0.07). Topping, regardless of number of pigs, did not affect (P > 0.23) any of the carcass traits measured. Topping improves growth performance of the remaining pigs. Based on IOFC, topping 2 pigs once is the most optimal. Improvements in performance from topping more than 2 pigs were not great enough to overcome the reduction in total weight produced by the pen.
Keywords: Growth; Marketing; Swine